2009
DOI: 10.1002/ar.20861
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes in the Mandible of Male Mice Associated With Aging and Biomechanical Stimulus

Abstract: Degenerative changes in the temporomandibular joint (TMJ) associated with aging can affect mandibular shape and reduce growth potential when stimulated by functional appliance therapy. This study was designed to evaluate the morphological changes in the mandibles of male mice associated with aging and biomechanical stimulus. Every 3 days over the course of 1 month, the lower incisors were trimmed by 1 mm to induce mandibular advancement (MA) when the animal was feeding. The left mandibles of the 23 experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…Male rats have also been used in previous studies on bone development because estrogen may potentially affect bone density. 21 However, mandibular advancement therapy is often used before the growth spurt, during which the level of estrogen does not differ significantly between genders. Therefore, female rats have also been used for research on mandibular growth in previous publications, 3,4,14 as well as in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Male rats have also been used in previous studies on bone development because estrogen may potentially affect bone density. 21 However, mandibular advancement therapy is often used before the growth spurt, during which the level of estrogen does not differ significantly between genders. Therefore, female rats have also been used for research on mandibular growth in previous publications, 3,4,14 as well as in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…This study has shown not only age-related but also stress-related changes in the morphological characteristics of the mandible. Many studies have been published regarding the morphological changes of the mandible during normal development (Bodner et al, 1998;Franchi et al, 2001;Lee et al, 2001;Ramaesh and Bard, 2003;Radlanski et al, 2003;Monteiro and Reis, 2005;Tagliaro et al, 2006Tagliaro et al, , 2009Pessa et al, 2008;Leamy et al, 2008). However, it remains unclear how to precisely detect abnormal morphology.…”
Section: Discussionmentioning
confidence: 99%
“…All these points were chosen according to their potential accuracy of digitization and because points were homologous through the structures, furthermore they would represent the mandible and its parts as good as possible: the mandible body ( corpus mandibulae, horizontal part, landmarks 1 to 5, and 15 to 18, these latter utilizing perpendicular projected points on the ventral border in relation to dental position, and 1, 4 and 5 recorded at the alveolar edges adjacent to the teeth) and ramus (ramus mandibulae, vertical part, landmarks 6 to 14). The chosen landmark configurations occupy different regions of the theoretical morphology defined by mandibular apparatus (11). No differences according to coat were considered.…”
Section: Methodsmentioning
confidence: 99%